Digital Leadership Strategy in Enhancing Technology-Integrated Pedagogical Practices in Vocational Education - Harefa, Mentari Indah Sehati; Bu'ulolo, Emiliana Mefita; Alhusori, Alhusori; Laia, Samarudin; Zebua, Risman Jaya; Pratiwi, Ika (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study aims to represent the phenomenon of school principals’ leadership strategies in enhancing collaborative organizational behavior among all school members at SMK Negeri 1 Amandraya. A phenomenological research design was employed using in-depth interviews and observations conducted at SMK Negeri 1 Amandraya. The participants consisted of ten teachers with more than five years of work experience at the school, selected through purposive sampling. Data were analyzed using narrative analysis, supported by data triangulation to ensure credibility. The findings indicate that the principal implemented three main strategies: (1) a digital managerial strategy through the optimization of platforms such as WhatsApp, Google Classroom, the school’s e-learning system, and virtual meetings for coordination; (2) an open communication strategy that promotes cross-functional collaboration through digital work groups; and (3) a collaborative culture-building strategy, characterized by habitual sharing of best practices and performance reflection via digital media. Collaborative organizational behavior was reflected in increased work motivation, more effective communication, and reduced internal conflict due to improved information transparency. The results further demonstrate that digital platform utilization strengthens collaborative work culture and enhances the quality of data-driven decision-making. This study recommends the implementation of continuous digital training, the development of standard operating procedures for digital collaboration, and the optimization of a platform-based work ecosystem to improve school organizational performance.